Efektivitas Lembar Kerja Peserta Didik (LKPD) Berbasis Kearifan Lokal dengan Pendekatan STEAM pada Materi Asam Basa - Salamiyah Salamiyah; Trining P Astutik; Ardian T Wicaksono (Chemistry Education Department of Education and Teaching Faculty, 2023)
Acid base material has difficulties in the concept of acid base strength and pH calculations. The test scores for acid-base material showed that 87% of the 68 students were below the KKM. Learning using LKPD based on local wisdom can make it easier for students to understand the material and improve learning outcomes. The STEAM approach can train students to apply their knowledge in making designs as a form of solving environmental problems by utilizing technology. The purpose of this study is to determine the effectiveness of LKPD. The type of research used is field research with the design used is the pretest posttest control group design. The sources in this study came from ten students of class XI IPA MAN Insan Cendekia Paser who were selected by simple random sampling. Data collection techniques, namely interviews, documentation, questionnaires and test questions, were then analyzed using the N-Gain test. The results of the study show the effectiveness of local wisdom-based LKPD with the STEAM approach in terms of learning outcomes showing an N-Gain value of 0.3 with the criteria of